$ε$-Isometries of convex bodies in $l^n_∞$ and $l^n_1$ - Vestfrid, Igor A. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5It is shown that every $ε$-isometry of a convex body in $l^n_∞$ or in $l^n_1$ can be well approximated by an affine surjective isometry.